Grimace scale, burrowing, and nest building for the assessment of post-surgical pain in mice and rats—A systematic review - Aulehner, Katharina; Leenaars, Cathalijn; Buchecker, Verena; Stirling, Helen; Schönhoff, Katharina; King, Hannah; Häger, Christine; Koska, Ines; Jirkof, Paulin; Bleich, André; Bankstahl, Marion; Potschka, Heidrun (Frontiers in Veterinary Science, 2022)
Several studies have suggested an informative value of behavioral and grimace scale parameters for the detection of pain. However, the robustness and reliability of the parameters as well as the current extent of implementation are still largely unknown. In this study, we aimed to systematically analyze the current evidence-base of grimace scale, burrowing and nest building for the assessment of post-surgical pain in mice and rats. The following platforms were searched for relevant articles: Pubmed, Embase via Ovid, and Web of Science. Only full peer-reviewed studies describing grimace scale, burrowing and/or nest building as pain parameters in the postsurgical phase in mice and/or rats were included. Information about the study design, animal characteristics, intervention characteristics, and outcome measures was extracted from identified publications. In total, 74 papers were included in this review. The majority of studies have been conducted in young adult C57BL/6J mice and Sprague Dawley and Wistar rats. While there is an apparent lack of information about young animals, some studies were identified that analyzed the grimace scale in aged rats. The majority of studies have focused on laparotomy-associated pain. Only limited information is available about other types of surgical interventions. While an impact of surgery and an influence of analgesia was rather consistently reported in studies focusing on grimace scales, the number of studies assessing respective effects was rather low for nest building and burrowing. Moreover, controversial findings were evident for the impact of analgetics on post-surgical nest building activity. Regarding analgesia, a monotherapeutic approach was identified in the vast majority of studies with non-steroidal anti-inflammatory (NSAID) drugs and opioids being most commonly used. In conclusion, most evidence exists for grimace scales, which were more frequently used to assess post-surgical pain in rodents than the other behavioral parameters. However, our findings also point to relevant knowledge gaps concerning the post-surgical application in different strains, age levels, and following different surgical procedures. Future efforts are also necessary to directly compare the sensitivity and robustness of different readout parameters applied for the assessment of nest building and burrowing activities.